2006
DOI: 10.1097/01.mlg.0000239108.12081.35
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen is Highly Effective in Pain Treatment After Endoscopic Sinus Surgery

Abstract: ESS is associated with significant postoperative pain. Acetaminophen provides adequate pain relief in most patients who have undergone ESS. However, the analgesic efficacy of acetaminophen alone is insufficient in some patients, and hence all patients with ESS must be followed closely to identify those patients in need of more efficient analgesia during the early phase of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 15 publications
(28 reference statements)
5
55
0
1
Order By: Relevance
“…Intravenous administration will achieve therapeutic plasma concentrations within 20 minutes of an initial dose, and concentrations remain therapeutic for around 2 hours post dose [17]. Paracetamol has been found to be highly effective in pain treatment after endoscopic sinus surgery [11]. Unlike our study, the control group received intravenous paracetamol after the surgery.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Intravenous administration will achieve therapeutic plasma concentrations within 20 minutes of an initial dose, and concentrations remain therapeutic for around 2 hours post dose [17]. Paracetamol has been found to be highly effective in pain treatment after endoscopic sinus surgery [11]. Unlike our study, the control group received intravenous paracetamol after the surgery.…”
Section: Resultsmentioning
confidence: 54%
“…While some are of the opinion that iv paracetamol is effective as a pre-emptive analgesic [9] others find no credibility [10]. Even though there are studies to show that intravenous paracetamol provides good analgesia in endoscopic sinus surgeries [11][12][13] there has been no study to study the preemptive effect of paracetamol in these surgeries. The purpose of the present study was to determine the post-operative analgesic Anaesthesia Section effects of pre-emptive iv paracetamol and the amount of reduction in tramadol consumption in FESS.…”
Section: Introductionmentioning
confidence: 99%
“…This study was a part of our Recovery After ESS study, and some other results have already been published 9 …”
Section: Methodsmentioning
confidence: 95%
“…Five randomized, placebo‐controlled trials were identified; all compared intravenous acetaminophen with placebo . The benefit of intravenous acetaminophen over its comparator in pain control and opioid consumption was not consistent across the studies.…”
Section: Clinical Trialsmentioning
confidence: 99%